2010
DOI: 10.1063/1.3339067
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of magnetically isotropic and anisotropic Nd–Fe–B permanent magnets prepared by spark plasma sintering technology

Abstract: Spark plasma sintering technique had been applied to prepare bulk isotropic and anisotropic nanostructured Nd–Fe–B permanent magnets via hot pressing and subsequent hot deformation process. Influences of processing conditions and deformation height reduction on the structure and magnetic properties of the magnets were investigated. For the hot deformed magnet with 80% height reduction, XRD patterns of the anisotropic magnets show dominant (00l) diffraction peaks indicating evident c-axis crystallographic align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 7 publications
0
13
1
Order By: Relevance
“…The remanence B r , intrinsic coercivity H cj , and maximum energy product (BH) max are 14.2 kGs, 12.9 kOe, and 50 MGOe, respectively. This energy product equals the previous energy-product record for die-upset Nd-Fe-B, achieved by Saito et al [10] and Liu et al [11]. The inset in Fig.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The remanence B r , intrinsic coercivity H cj , and maximum energy product (BH) max are 14.2 kGs, 12.9 kOe, and 50 MGOe, respectively. This energy product equals the previous energy-product record for die-upset Nd-Fe-B, achieved by Saito et al [10] and Liu et al [11]. The inset in Fig.…”
Section: Introductionmentioning
confidence: 60%
“…One method of achieving this goal is die-upsetting, where the c-axis of the grains is stressinduced and parallel to the press direction [7][8][9][10][11] and where the texture formation is caused by preferential grain growth via dissolution and precipitation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: ykfang@126.com. 0021-8979/2012/111(7)/07A734/3/$30.00 V C 2012 American Institute of Physics 111, 07A734-1 sintering technique 11 and produced from amorphous Nd-Fe-Co-Ga-B materials. 12 The obtained MFM images (10 lm  10 lm) are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It generates high frequency current and momentary local high temperature by joule heating and pulse energy, leading to the features of high heating speed, low sintering temperature, and short sintering time. In recent years, SPS has been widely applied to prepare bulk nanocrystalline Nd-Fe-B magnets [10][11][12]. In spite of similar raw materials and processing conditions, however, remarkable discrepancy in magnetic properties has been observed among different literatures [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SPS has been widely applied to prepare bulk nanocrystalline Nd-Fe-B magnets [10][11][12]. In spite of similar raw materials and processing conditions, however, remarkable discrepancy in magnetic properties has been observed among different literatures [10][11][12]. In their recent investigation, Huang et al found two zones with different grain sizes in the hot pressed and hot deformed magnets [13].…”
Section: Introductionmentioning
confidence: 99%